Near‐Surface Geophysics Perspectives on Integrated, Coordinated, Open, Networked (ICON) Science. Issue 3 (28th February 2022) - Salman, M.; Slater, L.; Briggs, M.; Li, L.
Abstract: Pointing to the Integrated, Coordinated, Open, Networked Findability, Accessibility, Interoperability, and Reusability (ICON‐FAIR) principles, we have determined several opportunities for implementation within the realm of near‐surface geophysics (NSG), representing a broad range of data acquisition and processing technologies. Our work explores the multifaceted community‐driven nature of NSG and, by applying ICON‐FAIR principles, we identify three key strategic objectives: (i) the development of an approach to integrating NSG into other geoscience data collection projects, (ii) the creation of coordinated and open standardized NSG data, and (iii) the networking of post‐secondary institutions to foster an equipment sharing consortium. The precedence within the geoscientific community demonstrates that there are significant opportunities for advancing interdisciplinary applications of NSG through the implementation of structural change within the ICON‐FAIR framework. Key Points: Near‐surface geophysics is a critical component to better understanding earth systems processes Standardizing practices and file‐formats will result in more cohesive and efficient science and knowledge production Inter‐institutional networking will facilitate equipment mobilization, and information sharing